Mobile IT in health – the case of short messaging service in an HIV awareness program. Issue 2 (3rd April 2018) - Bandyopadhyay, Tridib; Meso, Peter; Negash, Solomon
ABSTRACT: This study aims to augment our understanding of user intention to use mobile IT in health. Experiential dispositions and technology perceptions around a mobile service that is currently in use to access other value-seeking services are integrated to present an enriched characterization of intention to use m-health. Primary data from a pressing health context in a developing economy are collected to validate the model. The results demonstrate that previous experience from value services received on a mobile service enhances user attention, which in turn positively impacts the perceived usefulness of an incoming m-health program, which then influences user intention to adopt m-health services delivered on that mobile service. Overall, the findings provide a comprehensive understanding of user intention to accept m-health. Additionally, our results provide insights toward the choice of mobile technology and indicate aspects of message framing that may ensure practicable deployment and successful implementation of m-health programs.